PRAGMATIC CHARACTERISTICS OF DIPLOMATIC DISCOURSE - Yuldasheva Iroda Mamasharibovna (International Journal of Literature and Language Studies, 2026)
The analysis of linguistic, grammatical, and stylistic expression of communicative strategies and tactics used in diplomatic discourse was done based on a large number of examples chosen from real diplomatic documents (statements, conventions, manifestos, messages) and a survey of diplomats from various nations. The exploration of the language's syntactic structure in diplomatic documents highlighted the need to closely compare syntactic phenomena with morphological and lexical phenomena. Diplomatic documents serve as model texts for diplomatic discourse and are analyzed as such. The typology of diplomatic documents is described, their discursive qualities, styles, lexico-semantic, syntactic, and pragmatic features are examined, and suitable translation strategies are developed.